Long-Term Hydrologic Fluctuations and Dynamics of Primary Producers in a Tropical Crater Lake - Saulnier-Talbot, Émilie; Chapman, Lauren J.; Efitre, Jackson; Simpson, Kyle G.; Gregory-Eaves, Irene (Frontiers in Ecology and Evolution, 2018)
Aquatic ecosystems in tropical regions remain understudied and their long-term dynamics poorly understood. In East Africa, a better understanding of how natural communities of primary producers in small freshwater ecosystems respond to climatic variability is needed to improve management and conservation of aquatic resources. This study explored the response of algae and bacteria communities to marked hydrological variation over the past 1500 years in a small western Ugandan crater lake, Lake Nkuruba. We analyzed sedimentary algal and bacterial pigments to evaluate the magnitude and direction of change in the autotrophic community in response to severe climatic perturbations in the region. The lithology of the Lake Nkuruba sediment core indicated that external forcing in the form of a major drought, associated with the Medieval Climate Anomaly, caused a heavy, short-lived detrital pulse to the basin that led to a brief but substantial disruption of the lake system in the second half of the 13th century. The system appears to have recovered rapidly, and then transitioned to a more productive state than the one preceding the drought. The considerable variation observed in the sedimentary pigment biomarkers is likely linked with climatically-induced changes in the water column structure of this small crater lake. Our results highlight the challenge of defining appropriate baselines or reference conditions in climatically-sensitive East African aquatic ecosystems and disentangling long-term anthropogenic impacts from the strong regional hydrological flux at the decadal to centennial scale.